Appraisal of Triglyceride-Related Markers as Early Predictors of Metabolic Outcomes in the PREVIEW Lifestyle Intervention - Navas-Carretero, Santiago (2021)
Funding Information: The PREVIEW consortium would like to thank all the study participants at all intervention centers for their time and commitment and all scientists, advisors, and students for their dedication and contributions to the study. Specifically, we would like to thank Louise Dye (chairman of the Scientific Advisory Board, SAB), University of Leeds, UK, Richard Atkinson (Ethical Officer of the SAB), Virginia Commonwealth University, USA, and medical expert and consultant Stephen Colagiuri (University of Sydney, Australia). Meyers Madhus A/S is acknowledged for providing training and producing 2 cooking books. Furthermore, we gratefully thank the research staff from each center. From UCPH: Laura Pastor-Sanz, Grith M?ller, Lone Vestergaard Nielsen, Kasper Nowak, Arne Astrup, Finn Sand?-Pedersen, Morten Bo Johansen, Ulla Skovb?ch Pedersen, Maria Roed Andersen, Marianne Juhl Hansen, Jane J?rgensen, Sofie Skov Frost, and Lene Stevner. From HEL: Heikki Tikkanen, Saara Kettunen, Tiia Kunnas, Sanna Ritola, Laura Korpip??, Heini Hyv?rinen, Karoliina Himanen, Tiina Pellinen, Elina Malkam?ki, Heidi Jokinen, Pauliina Kokkonen, Liisi Korhonen, Jaana Valkeap??, Heli Pikkarainen, Martta Nieminen, Tuulia Ingman, Pihla M?kinen, and Sonja Toijonen. From UNOTT: Clare Randall, Nicky Gilbert, Shelley Archer, Sally Maitland, Melanie Marshall, Cheryl Percival, Jakki Pritchard, Laura Helm, and Peter Mansell. From UNAV: Blanca Martinez de Morentin, Maria Hernandez Ruiz de Eguilaz, Salome Perez Diez, Veronica Ciaurriz, Angels Batlle, and Maria Jose Cobo. From MU: Georgi Bogdanov, Pavlina Gateva, Rossica Metodieva, and Galia Dobrevska. From SU: Nils Swindell, Jeff Stephens, Gareth Dunseath, Steve Luzio, and Masoumeh Minou. From THL: Jouko Soundvall, Laura Ram?n, Merja Tukiainen, Ira Greinert, Laura Karjalainen, and Jukka Lauronen. From UNSYD: Fiona Atkinson, Michele Whittle, Jessica Burke, Kylie Simpson, Kimberley Way, Sally McClintock, Radhika Seimon, Shelly Keating, Kirsten Bell, Tania Markovic, Cathy Corry, Evalyn Eldering, and Ian Caterson. From UOA: Lindsay Plank, Nicholas Gant, Jon Woodhead, Anne-Thea McGill, Katya Volkova, Madhavi Bollineni, Clarence Vivar, Kelly Storey, Niamh Brennan, and Audrey Tay. Publisher Copyright: Copyright © 2021 Navas-Carretero, San-Cristobal, Siig Vestentoft, Brand-Miller, Jalo, Westerterp-Plantenga, Simpson, Handjieva-Darlenska, Stratton, Huttunen-Lenz, Lam, Muirhead, Poppitt, Pietiläinen, Adam, Taylor, Handjiev, McNarry, Hansen, Brodie, Silvestre, Macdonald, Boyadjieva, Mackintosh, Schlicht, Liu, Larsen, Fogelholm, Raben and Martinez.